Fra-1 replaces c-Fos-dependent functions in mice - Fleischmann, Alexander (Cold Spring Harbor Laboratory Press, 2000)
Structure–function analysis as well as studies with knock-out and transgenic mice have assigned distinct functions to c-Fos and Fra-1, two components of the transcription factor AP-1 (activator protein-1). To test whether Fra-1 could substitute for c-Fos, we generated knock-in mice that express Fra-1 in place of c-Fos. Fra-1 rescues c-Fos-dependent functions such as bone development and light-induced photoreceptor apoptosis. Importantly, rescue of bone cell differentiation, but not photoreceptor apoptosis, is gene-dosage dependent. Moreover, Fra-1 fails to substitute for c-Fos in inducing expression of target genes in fibroblasts. These results show that c-Fos and Fra-1 have maintained functional equivalence during vertebrate evolution.